Patellofemoral pain, body morphology and alignment in female pubertal dancers: One-year follow-up - Steinberg, N.; Tenenbaum, S.; Stern, M.; Zeev, A.; Siev-Ner, I. (Journal of Sports Sciences, 2019)
The aim of this study was to assess changes in body morphology, anatomical alignment and prevalence of patellofemoral pain (PFP) in young female dancers along one year of pubertal growth, and to identify the risk factors related to PFP in these young dancers. Both legs of 60 dancers were evaluated during grade 7 and again after 1-year. At each of these points in time, the dancers were interviewed concerning their background, and anthropometric measurements, lower-limb physical examinations and knee ultrasound scans were performed. Morphological parameters changed significantly from baseline to follow-up. PFP was found in 53.3% of the dancers` knees at baseline. At follow-up, 55.4% of the asymptomatic knees at baseline developed PFP, and only 9.4% of the symptomatic knees at baseline recovered. Lower BMI was identified among dancers who developed PFP during follow-up compared with dancers with no PFP, either at baseline or at follow-up. A positive grinding and positive Patellar Inhibition Test (PIT) were found to be risk factors for PFP at follow-up. A high prevalence of young dancers suffered PFP, from injuries they sustained mostly during the 1-year of dance practice. Parameters predisposing the dancers to PFP should be identified at early stages of dance class.